2018
DOI: 10.1007/s41547-017-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive erbium flap (MINIETM flap)—a retrospective surgical treatment for chronic periodontitis

Abstract: This clinical retrospective split-mouth study was designed to evaluate the efficacy of two (FDA approved) erbium laser wavelengths in a minimally invasive flapped approach for the treatment of generalized chronic periodontitis. Twenty-eight (28) patients diagnosed with generalized chronic periodontitis with pocket depths ranging from 4 to 9 mm had 551 posterior teeth surgically treated in a minimally invasive manner and were followed over 6 months. Minimally invasive erbium (MINIE) flaps were performed in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…They also concluded that in comparison to those traditional techniques, no significant change in terms of recession in patients treated with the minimally invasive erbium flap technique was observed over a six-month period. 46 These researchers had used hand instruments and ultrasonic devices for calculus removal after raising the periodontal flaps and laser only for smear layer removal, However, in the current study we used the laser irradiation for removal of any remaining calculus in hard-to-reach areas with a lower frequency setting of the device and then the setting was adjusted to a higher frequency to achieve a smoother root planing surface and detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that in comparison to those traditional techniques, no significant change in terms of recession in patients treated with the minimally invasive erbium flap technique was observed over a six-month period. 46 These researchers had used hand instruments and ultrasonic devices for calculus removal after raising the periodontal flaps and laser only for smear layer removal, However, in the current study we used the laser irradiation for removal of any remaining calculus in hard-to-reach areas with a lower frequency setting of the device and then the setting was adjusted to a higher frequency to achieve a smoother root planing surface and detoxification.…”
Section: Discussionmentioning
confidence: 99%